ESTIMASI NILAI REPITABILITAS DAN PERFORMA PRODUKSI UMUR LAHIR DAN SAPIH INDUK BABI PERANAKAN LANDRACE (The estimate of repitability value and performances at birth and weaning age of landrace crossbred) - Yohanes Djego; Johny N. Kihe; Petrus Kune (JURNAL NUKLEUS PETERNAKAN, 2022)
The aims of this research were to estimate repitability coefficients of production at birth and weaning characters and to determine the average and standard deviation of landrace crossbreed sows. This research was carried out in two breeding farms namely the Instalation of Pig Breeding, village of Tarus, Kupang Regency and the Manise Pig Farm, Village of Oetete, Kupang City, East Nusa Tenggara. Materials used 15heads landrace crossbreed sows ( 15 heads ) which born and weaned piglets during the study periode. The number of piglets for the first parity was 151heads and for the second parity was 162heads. All sows was mated by artivicial insemination with boars of landrace crossbreed. Variables were liter size, weaning rate, birth weight, weaning weight and weaning rate. Results showed that landrace crossbreed sows had the average and deviation standard for the first and second liter size were 10.00±1.50heads and 10.73±2.40heads, respectively; for the first and second birth weight were 1.37±0.23kg and 1.68±0.34kg, respectively; for the first and second weaning weight were 6.42±0.38kg and 6.72±0.51kg, respectively and for the first and second weaning rate were 8.33±1.28heads and 8.68±1.43 heads; respectively. The average of litter size, birth weight, weaning weight and weaning rate between the first and second parity was no difference (P > 0,05). The value of repeatabitily for characters of liter size, birth weight, weaning weight and weaning rate were 0.32; 0.47; 0.49 and 0,42; respectively. In conclusion, the repeatabily value of litter size, birth weight, weaning weight and weaning rate from landrace crossbred sows were medium value and the performance of those characters between the first and second parity were no difference.